Persepsi Mahasiswa FEB Unwira Kupang terhadap Investasi dan Dampaknya terhadap Pertumbuhan Ekonomi Indonesia - Lonak, Putri Debora; Suban, Maria Petrosia Peni; Mulik, Cindy Esterina N.; Lawalu, Emiliana Martuti (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Economic growth is a key indicator of a nation's progress, with investment playing a strategic role as a primary driver. However, investment literacy among university students, particularly in eastern regions of Indonesia such as Kupang, remains relatively low. This study aims to explore the perceptions of students at the Faculty of Economics and Business (FEB), Widya Mandira Catholic University (Unwira) Kupang regarding investment and its impact on Indonesia's economic growth. Using a qualitative approach with a phenomenological method, the research involved semi-structured interviews with 12 students and two focus group discussions (FGDs) involving 10–15 participants each, selected based on their interest and preliminary knowledge in finance and investment. The findings indicate that most students recognize the importance of investment in economic development but have limited understanding of investment instruments, mechanisms, and associated risks. A lack of financial literacy is identified as a major barrier, although students expressed strong interest in gaining further knowledge. They also perceive investment as closely linked to macroeconomic progress, especially in job creation and infrastructure development. The study concludes that while perceptions are generally positive, structured and practical financial literacy programs are needed to bridge knowledge gaps. Such initiatives can empower students to become confident, informed investors contributing to inclusive and sustainable economic growth.